Favorable Interactions between Enfuvirtide and 1-β-d-2,6-Diaminopurine Dioxolane In Vitro - Tremblay, Cécile L. (American Society for Microbiology, 2003)
We evaluated the in vitro anti-human immunodeficiency virus type 1 (HIV-1) interactions between 1- β-d-2,6-diaminopurine dioxolane (DAPD) and enfuvirtide (T-20) against clinical isolates sensitive and resistant to reverse transcriptase and protease inhibitors. Interactions between T-20 and DAPD were synergistic to nearly additive, with combination index values ranging from 0.53 to 1.06 at 95% inhibitory concentrations. These studies suggest that a combination of T-20 and DAPD might be useful in the treatment of antiretroviral drug-experienced patients.